Functional remediation components: A conceptual method of evaluating the effects of remediation on risks to ecological receptors. Issue 21 (1st November 2016) - Burger, Joanna; Gochfeld, Michael; Bunn, Amoret; Downs, Janelle; Jeitner, Christian; Pittfield, Taryn; Salisbury, Jennifer
ABSTRACT: Governmental agencies, regulators, health professionals, tribal leaders, and the public are faced with understanding and evaluating the effects of cleanup activities on species, populations, and ecosystems. While engineers and managers understand the processes involved in different remediation types such as capping, pump and treat, and natural attenuation, there is often a disconnect between (1) how ecologists view the influence of different types of remediation, (2) how the public perceives them, and (3) how engineers understand them. The overall goal of the present investigation was to define the components of remediation types (= functional remediation). Objectives were to (1) define and describe functional components of remediation, regardless of the remediation type, (2) provide examples of each functional remediation component, and (3) explore potential effects of functional remediation components in the post-cleanup phase that may involve continued monitoring and assessment. Functional remediation components include types, numbers, and intensity of people, trucks, heavy equipment, pipes, and drill holes, among others. Several components may be involved in each remediation type, and each results in ecological effects, ranging from trampling of plants, to spreading invasive species, to disturbing rare species, and to creating fragmented habitats. In some cases remediation may exert a greater effect on ecological receptors than leaving the limited contamination in place. A goal of this conceptualization is to break down functional components of remediation such that managers, regulators, and the public might assess the effects of timing, extent, and duration of different remediation options on ecological systems.